Money and capital markets : financial institutions and instruments in a global marketplace - Rose, Peter S. (Boston : Irwin/McGraw-Hill, 2000)
Business
Keywords: Money market; Capital market; Fianancial institution; Global market; Global financial systems; Banking; monetary policy; Financial market; International banking